2023
DOI: 10.1123/japa.2022-0064
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Determinants of Exercise-Related Affective Valence in Regular Exercisers Between the Ages of 55 and 69 Years

Abstract: This study aimed to understand determinants of recalled in-task affective valence experienced during a regularly performed aerobic bout in adult exercisers aged 55+. Qualitative data were collected (January to March, 2021, during the COVID-19 pandemic) using interviews wherein individuals (N = 16, 69% women, 61 ± 5 years) recalled deviations in affective valence in response to a regularly completed bout. Using thematic analyses, two themes emerged regarding how COVID-19 impacted regular exercise behaviors: (a)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 74 publications
0
1
0
Order By: Relevance
“…The current analyses also revealed that the nomothetic interpretation that physical readiness had almost no association with recalled affective valence. This lack of association opposes a growing body of qualitative findings, which identify factors underlying perceptions of physical readiness (e.g., energy, fitness, body integrity) as influencing physical activity-related cognitions and affective experiences [ 61 63 ]. Relying solely on the nomothetic interpretation, a client’s poor perception of physical readiness may not dissuade a practitioner from imposing a scheduled, more strenuous exercise session–potentially eliciting a rather unpleasant experience.…”
Section: Discussionmentioning
confidence: 99%
“…The current analyses also revealed that the nomothetic interpretation that physical readiness had almost no association with recalled affective valence. This lack of association opposes a growing body of qualitative findings, which identify factors underlying perceptions of physical readiness (e.g., energy, fitness, body integrity) as influencing physical activity-related cognitions and affective experiences [ 61 63 ]. Relying solely on the nomothetic interpretation, a client’s poor perception of physical readiness may not dissuade a practitioner from imposing a scheduled, more strenuous exercise session–potentially eliciting a rather unpleasant experience.…”
Section: Discussionmentioning
confidence: 99%